Comparative Study of Soil Organic Carbon in Forest of National Park and Sacred Grove in Kathmandu Valley - Wagle, Prakash Chandra (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
Soil organic carbon (SOC) represents a significant fraction of the global carbon pool and is vital for understanding the ecosystem functions that occur in soils. Forest types and management can have a significant impact on soil organic matter and, as a result, soil organic carbon. However, comparative studies of SOC with respect to forest management have been carried out to a limited extent. Thus, the study was carried out in the Shivapuri-Nagarjun forest and the pine forest of Gokarneshwor with the aim of comparing the SOC of the Shivapuri forest of Shivapuri Nagarjun National Park and the pine forest of Gokarneshwor. Soil samples were collected by the stratified random sampling method. The composite samples from the depths of 0–10 cm and 10–15 cm were taken, mixed properly, air dried, and tested in the laboratory. Soil organic carbon was measured using the modified Walkley and Black methods. The soil organic carbon of the Shivapuri-Nagarjun forest was found to be 91.11 tons/ha, and the pine forest was found to be 34.77 tons/ha on average. Further analysis interlinking plant residue and microbial activities and their implications for soil organic carbon could be beneficial in forest management decisions